[OP.6A.06] PREVALENCE AND CLINICAL CHARACTERISTICS OF TRUE MASKED HYPERTENSION COMPARED TO REVERSE AND ISOLATED NOCTURNAL MASKED HYPERTENSION. (September 2017) - Tocci, G.; Attalla, N.; Simonelli, F.; Presta, V.; Figliuzzi, I.; Gallo, G.; Costanzi, V.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Masked hypertension (MHT) is characterized by normal clinic blood pressure (BP) and above normal 24-hour ambulatory BP levels. Potential clinical impact of this condition is still debated. Aim: To evaluate prevalence, characteristics and clinical outcomes of different forms of MHT. Design and method: We analysed data derived from a large cohort of adult individuals, who consecutively underwent home, clinic and ambulatory BP monitoring at our Hypertension Unit. All BP measurements were performed and BP thresholds were set according to recommendations from European guidelines. Study population was stratified into 3 groups: 1) truly MHT (tMHT): clinic BP <140/90 mmHg, 24-hour BP > = 130/80 mmHg, non-dipping status; 2) isolated nocturnal MHT (inMHT): clinic BP <140/90 mmHg, 24-hour BP > = 130/80 mmHg, dipping status; 3) reverse nocturnal MHT (rnMHT): clinic BP <140/90 mmHg, 24-hour BP > = 130/80 mmHg, reverse dipping status. Results: From an overall sample of 5, 634 adult individuals who underwent full BP assessment at our Unit we selected 2, 413 (42.8%) untreated adult individuals, among whom 152 (6.3%) had MHT. In this latter group, 64 (42.1) had tMHT, 71 (46.7%) had inMHT, and 15 (9.9%) had rnMHT. No significant differences were found among groups regarding demographic, clinical characteristics and prevalence of risk factors, excluding older age in rnMHT (67.412.9 years; P<0.001) and higher prevalence of diabetes in tMHT (10.9%; P < 0.05) compared to other groups. No significant differences were found among groups for home and clinic BP. Night-time systolic/diastolic BP levels and loads showed a significant trend toward increase from inMHT to tMHT towards rnMHT; whereas systolic/diastolic BP fall showed a significant opposite trend. tMHT was associated to a borderline risk of stroke (OR 0.13; 95% IC 0.013–1.296; P = 0.082) and hospitalization for hypertension (OR 0.413; 95% IC 0.146–1.172; P = 0.097). Conclusions: Further studies are needed with larger population sample and higher number of cardiovascular events to better evaluate the potential prognostic impact of different forms of MHT in the clinical practice.